2020
DOI: 10.3389/fncel.2020.00175
|View full text |Cite
|
Sign up to set email alerts
|

Truncated Tau Induces Mitochondrial Transport Failure Through the Impairment of TRAK2 Protein and Bioenergetics Decline in Neuronal Cells

Abstract: Truncated Tau Affects Mitochondrial Transport and reduction of ATP production available for the process of movement of these organelles. These observations are novel and represent a set of exciting findings whereby tau pathology could affect mitochondrial distribution in neurons, an event that may contribute to synaptic failure observed in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 61 publications
5
31
0
Order By: Relevance
“…Importantly, we have demonstrated that the expression of caspase-3 cleaved tau in neuronal cell lines and primary neurons negatively affects mitochondrial health in response to calcium stress and Aβ treatment [9,11]. Furthermore, mitochondrial impairment induced by pathological modifications of tau can also affect neuronal communication [12][13][14]. Moreover, the expression of caspase-3 cleaved tau affected mitochondrial health-inducing depolarization and mitochondrial fragmentation by impairing the mitochondrial fusion regulator Opa1 [9,12,15].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Importantly, we have demonstrated that the expression of caspase-3 cleaved tau in neuronal cell lines and primary neurons negatively affects mitochondrial health in response to calcium stress and Aβ treatment [9,11]. Furthermore, mitochondrial impairment induced by pathological modifications of tau can also affect neuronal communication [12][13][14]. Moreover, the expression of caspase-3 cleaved tau affected mitochondrial health-inducing depolarization and mitochondrial fragmentation by impairing the mitochondrial fusion regulator Opa1 [9,12,15].…”
Section: Introductionmentioning
confidence: 92%
“…Conditionally immortalized cortical neurons (CN1.4) [10,13] were cultured in 1×Dulbecco's modified Eagle's medium with high glucose (DMEM) (Mediatech CellGro, Corning, NY, USA), supplemented with 5% inactivated fetal bovine serum (Mediatech Inc., Manassas, VA, USA) with 1% penicillin/streptomycin (Mediatech Inc., CellGro, Corning, NY, USA), and incubated at 33 • C and 5% CO 2 . In addition, these cells were transiently transfected with plasmids containing GFP, GFP-full-length tau (GFP-T4), and GFP-caspase-3 cleaved tau (GFP-T4C3), and after 48 h, transfected cells were treated with 10 µm of SFN (ChemCruz, Santa Cruz Biotechnology, Dallas, TX, USA) for 24 h.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations
“…Hyperphosphorylated tau causes microtubule instability, which leads to neuronal synaptic disruption, connectivity and plasticity damage, neuronal death ultimately. A study has shown that caspase-cleaved tau increases TRAK2-mitochondria binding and decreases the ATP production available for the locomotion of these organelles, resulting in adverse effects on mitochondrial transport (Quintanilla et al, 2020).…”
Section: Alzheimer's Diseasementioning
confidence: 99%